STRUCTURE AND QUALITY NETWORKS OF ALCOHOLICS ANONYMOUS - Nava Quiroz, Carlos; Vega Valero, Zaira (Anales de Psicología / Annals of Psychology, 2006)
The objective of this work was to evaluate the structural properties and social participation of anonymous alcoholic group (AA) and comparing them against those of nonalcoholic (NA). The results showed that although the AA had at least two years without still drinking displayed important differences respect to the NA in the average of social and struc-tural participation. The discussion is centered in the social participation and the social isolation like alternative element that allows to understand thorough more the phenomenon of the alcoholism.